Astronomical and glacial forcing of East Asian summer monsoon variability. (1st May 2015) - Sun, Youbin; Kutzbach, John; An, Zhisheng; Clemens, Steven; Liu, Zhengyu; Liu, Weiguo; Liu, Xiaodong; Shi, Zhengguo; Zheng, Weipeng; Liang, Lianji; Yan, Yan; Li, Ying
Abstract: The dynamics of glacial–interglacial monsoon variability can be attributed to orbitally induced changes in summer insolation and internal boundary conditions. However, the relative impacts of astronomical and internal factors on East Asian summer monsoon variability remain controversial. Here we combine proxy data and model results to evaluate the response of East Asian summer monsoon change to these forcings. δ 13 C of loess carbonate, a sensitive summer monsoon proxy from the western Chinese Loess Plateau, demonstrates coexistence of distinct 100-, 41- and 23-ka periods, in contrast to precession-dominated speleothem δ 18 O records in South China. Model results indicate that insolation, ice and CO2 have distinct impacts on summer precipitation changes in East Asia, whereas their relative impacts are spatially different, with a relatively stronger insolation effect in south China and a more dominant ice/CO2 influence in north China. Combined proxy data and model results indicate that East Asian summer monsoon variability was induced by integrated effects of summer insolation and changing boundary conditions (e.g., ice sheets and CO2 concentration). Our proxy-model comparison further suggests that gradual weakening of the summer monsoon related to slowly decreasing summer insolation at astronomical timescales will be likely overwhelmed by the projected ongoing anthropogenic CO2 emissions. Highlights: Summer monsoon variability was reconstructed using δ 13 C records of loess carbonates. Two δ 13 C time series exhibit glacial–interglacial to precessional monsoon variability. Asian summer monsoon variability is sensitive to astronomical and glacial forcing. Proxy-model comparison predicts increased summer precipitation over the next century.